Light and ultrastructural analysis of Myxobolus insignis (Myxozoa), infecting the Amazonian Fish Semaprochilodus insignis (Prochilodontidae) - Azevedo, Carlos; Clemente, Sérgio C.s.; Casal, Graça; Matos, Patrícia; Oliveira, Elsa; Al-Guraishy, Saleh; Matos, Edilson (Zootaxa, 2012)
A myxosporean infecting the gill filaments of the freshwater teleost Semaprochilodus insignis collected in the TrombetasRiver (Central Amazonian Region, Brazil) is described using light and electron microscopy. The spores were ovoid infrontal view with round extremities and measured 15.4 ± 0.6μm in total length, 12.4 ± 0.5μm wide and 8.1 ± 0.7μmthick; the spore valves (up to 0.4μm) were surrounded by an uniform dense layer with variable thickness up to ~1.0μm)due to the presence of a complex network of anastomosed microfibrils closely adherent to the valves. Two symmetric polarcapsules measured 5.9 ± 0.4μm long and 3.4 ± 0.5μm wide, each having a polar filament with 7-8 coils slightly obliquelyto the longitudinal axis of the polar capsule. The polar capsule wall measured ~0.4μm thick and was constituted by a hy-aline substance (~0.25μm thick) surrounded by a layer of electron dense granular material (~0.15μm thick). In this paper the Amazonian region, which was previously described based on light microscopy (Eiras et al. 2005b).we present, by the first time, ultrastructural aspects of the spores of Myxobolus insignis found in a teleost collected from